RESEARCH INTO VISUAL-MOTOR MONITORING BY OPERATORS OF MOBILE OBJECTS - Petukhov, Igor; Steshina, Lyudmila; Kurasov, Pavel; Chernykh, Dmitriy; Tanryverdiev, Il'ya (Journal of Applied Engineering Science, 2017)
The paper presents a new model of the visual-motor monitoring which features two control loops - objective and subjective ones. This model allows to explain the phenomenon of cognitive dissonance that is experienced by operators in solving sophisticated problems. The results of experimental studies comprising the control of an object under conditions of the objective and subjective control are presented.